KARAKTERISTIK ALIRAN PLUG AIR-UDARA PADA PIPA BERDIAMETER KECIL DAN HORISONTAL - , BILHAN GAMALIEL HARTANTO, Dr. Eng. Deendarlianto, ST., M.Eng. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Slug flow in a multi-phase flow pattern of piping systems should be avoided because it can lead to blasting pipe, structural failure due to vibration, or lead to corrosion caused by cavitation. Plug flow is a part of the slug flow. Plug flow is transition of flow pattern from stratified to slug flow. It has simillar characteristics with slug flow and it has also potensial danger in nuclear reactor on loss of coolant accident (LOCA) case. Plug flow can be seen with visualization and signal analysis method. In this study, characteristic of plug flow and effects due to changes pipe diameter was investigated. The plug flow mechanism was studied by change the superficial velocity of gas (JG) from 0,12 to 0,70 m/s on change of liquid superficial velocity (JL) from 0,25 m/s to 1,13 m/s for each pipe diameter of 16 and 26 mm. The CECM (constant electric current method) method is compared with the visualitation method. The result of CECM is used to analysis liquid hold up, cross correlation, Probability Distribution Function (PDF), and Power Spectra Density (PSD). From the analysis is known that the higher of gas velocity superficial, the higher of velocity of gas plug for each pipe diameter. Liquid hold up is indicating transient characteristic of plug flow. The result of visualitation methode is used to analysis shape and size plug, wave frequency and wave velocity. From the analysis is known that the shape and size of the plug in the pipe diameter 16 mm is smaller compare with pipe diameter 26 mm. The pipe diameter 16 mm produces more plug than pipe diameter 26 mm, it caused higher wave frequency than pipe diameter 26 mm.